"No One in the House Knew Her Name": Servant Problems in R. K. Narayan's Short Stories. Issue 3 (2nd October 2018) - Hai, Ambreen
Abstract: The invisibility and precarity of domestic servants in South Asia remains a pervasive societal and political problem, not often addressed in South Asian literary studies. This essay analyses four short stories by R. K. Narayan that center on marginal, subaltern servant figures, male and female, young and old. It makes two related arguments: one, that Narayan uses the short story form (as opposed to the novel) to give unusual compassionate attention to these servant figures, and to critique the arrogance and injustice of the employer class; and two, that Narayan's mode of representation, with its limitation to upper class narrators' perspectives, creates a distance from the very figures it seeks to delineate, sometimes reinforcing the very class biases or suspicions of the servants that it attempts to question. Emphasizing attentiveness to forms of narration as well as to content as a reading strategy, this essay assesses both the interventions and limitations of Narayan's portrayal of servants in his fiction.